2003
DOI: 10.1038/sj.ejcn.1601604
|View full text |Cite
|
Sign up to set email alerts
|

Preterm infant formula supplementation with α linolenic acid and docosahexaenoic acid

Abstract: Objective: To investigate if supplementation of preterm infant formula with a high docosahexaenoic acid/eicosapentaenoic acid (DHA/EPA) ratio together with a-linolenic acid (ALA) was able to maintain plasma and red blood cell DHA levels similar to that obtained with breast milk feeding without altering n-6 fatty acid status. Design and subjects: Preterm infants of mothers who elected not to breast feed (n ¼ 13) were assigned to ALA-and DHAenriched formula (DHA group: DHA/EPA ¼ 5/l). Infants fed breast milk (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
1
3
1
1
Order By: Relevance
“…RBC-AA at 1 month of age was also found to be negatively associated with BSID-III receptive language and fine motor abilities at 1 year corrected age, but no associations were observed for DHA. The lack of a significant associations between breast-milk or RBC-DHA and developmental outcome are in line with previous observations [40][41][42], although some studies have demonstrated beneficial effects of DHA on psychomotor development in both term and preterm infants [35,[43][44][45]. A recent Swedish study found significant correlations between breast-milk AA and developmental outcomes at 40 weeks gestational age in preterm infants (born in gestational week 24-36) using the Brazelton Neonatal Behavioral Assesment Scale, which is very similar to the NNNS [16].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…RBC-AA at 1 month of age was also found to be negatively associated with BSID-III receptive language and fine motor abilities at 1 year corrected age, but no associations were observed for DHA. The lack of a significant associations between breast-milk or RBC-DHA and developmental outcome are in line with previous observations [40][41][42], although some studies have demonstrated beneficial effects of DHA on psychomotor development in both term and preterm infants [35,[43][44][45]. A recent Swedish study found significant correlations between breast-milk AA and developmental outcomes at 40 weeks gestational age in preterm infants (born in gestational week 24-36) using the Brazelton Neonatal Behavioral Assesment Scale, which is very similar to the NNNS [16].…”
Section: Discussionsupporting
confidence: 79%
“…The individual levels of both LA, AA and DHA in the RBC from the infants in the present study tended to be higher than that reported in more preterm populations [35][36][37], but resembled reported levels in RBC from both Danish [25] and American term infants [38,39]. The fatty acid composition of the infant RBC at 1 month of age was found to reflect that a considerable proportion of the infants were to some extent formula fed.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…44 Dependendo das quantidades e proporções entre os nutrientes utilizados no enriquecimento, os resultados no desenvolvimento infantil podem se aproximar daqueles obtidos com aleitamento materno exclusivo. 45 A suplementação deve ser vista com cautela, pois dependendo das quantidades e tipos de AGPICL, pode-se inibir a conversão de ω -6 em ácido araquidônico ou o alto teor de EPA pode competir com o AA pela incorporação de fosfolipídios nos tecidos. 5,15,31 Portanto, as fórmulas devem conter, preferencialmente, AA e DHA, sendo que as quantidades devem ser próximas daquelas encontradas no leite materno 1,21 (Tabela 3).…”
Section: Conclusõesunclassified
“…One such improvement consists in adding LC-PUFA to IF, since several studies on infant nutrition have addressed their beneWcial eVects on growth and development. Moreover, the addition of docosahexaenoic acid (DHA, C22:6n ¡ 3) to IF has demonstrated improved neurofunctional response in pre-term infants (Cunnane et al, 2000;Gibson, Neumann, & Makrides, 1996;Hornstra, Al, van Houwelingen, & Foreman van Drongelen, 1995;Rodriguez et al, 2003;Valenzuela & Nieto, 2001). One source of DHA is Wsh oil, though it remains very susceptible to oxidation due to high PUFA content.…”
Section: Introductionmentioning
confidence: 97%